Electrochemical oxidation of COD from real textile wastewaters: Kinetic study and energy consumption. (March 2017) - Zou, Jiaxiu; Peng, Xiaolan; Li, Miao; Xiong, Ying; Wang, Bing; Dong, Faqin; Wang, Bin
Abstract: In the present study, the electrochemical oxidation of real wastewaters discharged by textile industry was carried out using a boron-doped diamond (BDD) anode. The effect of operational variables, such as applied current density (20–100 mA·cm −2 ), NaCl concentration added to the real wastewaters (0–3 g·L −1 ), and pH value (2.0–10.0), on the kinetics of COD oxidation and on the energy consumption was carefully investigated. The obtained experimental results could be well matched with a proposed kinetic model, in which the indirect oxidation mediated by electrogenerated strong oxidants would be described through a pseudo-first-order kinetic constant k . Values of k exhibited a linear increase with increasing applied current density and decreasing pH value, and an exponential increase with NaCl concentration. Furthermore, high oxidation kinetics resulted in low specific energy consumption, but this conclusion was not suitable to the results obtained under different applied current density. Under the optimum operational conditions, it only took 3 h to complete remove the COD in the real textile wastewaters and the specific energy consumption could be as low as 11.12 kWh·kg −1 COD. The obtained results, low energy consumption and short electrolysis time, allowed to conclude that the electrochemical oxidation based on BDD anodes would have practical industrial application for the treatment of real textile wastewater. Highlights: Real textile wastewaters were electrooxidized using BDD anode. COD oxidation could be well fitted using a modified kinetic model. High COD removal rates were attained with adding NaCl and in acidic media. Low energy consumption and short electrolysis time could be obtained under the optimizing conditions.